RETRACTED: Synthesis of efficient cobalt–metal organic framework as reusable nanocatalyst in the synthesis of new 1,4-dihydropyridine derivatives with antioxidant activity - Salahdin, Omar dheyauldeen; Patra, Indrajit; Ansari, Mohammad Javed; Emad Izzat, Samar; Uktamov, Khusniddin Fakhriddinovich; Abid, Mohammed Kadhem; Mahdi, Ahmed B.; Hammid, Ali Thaeer; Mustafa, Yasser Fakri; Sharma, Himanshu (Frontiers in Chemistry, 2022)
Efficient cobalt -metal organic framework (Co-MOF) was prepared by controllable- microwave assisted reverse micelle synthesis route. The products were characterized by SEM image, N2 adsorption/desorption isotherm, FTIR spectrum and TG analysis. Results showed that the products have small particle size distribution, homogenous morphology, significant surface area and high thermal stability. The physicho-chemical properties of the final products were remarkable compared to other MOF samples. The newly synthesized nanostructures were used as recyclable catalysts in the synthesis of 1,4-dihydropyridine derivatives. After the confirmation of related structures, antioxidant activity of derivatives based on DPPH method were evaluated and the relationship between structures and antioxidant activity were observed. In addition to recyclability, the catalytic activity of Co-MOF studied in this research, has remarkable effects on the synthesis of 1,4 dihydropyridine derivatives.